Correlation of Serum Galectin-3 Levels with Ejection Fractions in Healthy Subjects and Heart Failure Patients - Amber Naureen, Khurram Munir, Abdur Rauf Hammad, Muhammad Sajid Khan, Mahwash Mengal, Muhammad Alam Mengal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was twofold: (1) to evaluate Galectin-3's use as a prognostic or predictive biomarker in HF, and (2) to compare eject fractions (EF) in healthy individuals to those in HF patients by analysing the correlation between blood Galectin-3 levels and EF. Study Design: The study was a cross-sectional observational analysis of two groups with similar demographics (n=150 each): healthy people and HF patients. Transthoracic echocardiography was used to assess EF, while enzyme-linked immunoassay assay (ELISA) was used to assess galectin-3 levels. Study Setting and Duration: The study was carried at Fatima Jinnah Medical University Lahore over a 12-month period from January 2022 to December 2022. Results: Serum Galectin-3 levels were significantly higher in HF patients (mean±SD: 26.4±7.2 ng/mL) compared to healthy subjects (mean±SD: 12.1±2.8 ng/mL; p<0.001). There was a strong inverse correlation between Galectin-3 levels and EF in HF patients (r=-0.72, p<0.001), while a weak correlation was observed in healthy subjects (r=-0.26, p=0.002). A receiver operating characteristic (ROC) curve analysis demonstrated that Galectin-3 could distinguish HF patients from healthy subjects with an area under the curve (AUC) of 0.92 (95% CI: 0.89-0.95, p<0.001), suggesting its potential as a diagnostic biomarker. Moreover, elevated Galectin-3 levels were independently associated with a higher risk of HF-related hospitalizations and mortality (HR: 1.35, 95% CI: 1.12-1.63, p=0.002), indicating its prognostic value. Conclusion: Serum Galectin-3 levels were shown to be significantly inversely correlated with EF in both healthy people and HF patients, with the connection being higher in the latter group. More exploration in bigger cohorts and prospective studies is warranted since galectin-3 emerges as a viable diagnostic and prognostic biomarker in HF. Keywords: Galectin-3, ejection fraction, heart failure, biomarker, diagnosis, prognosis, transthoracic echocardiography, enzyme-linked immunosorbent assay.